Boyhood [videorecording (DVD)] - Coltrane, Ellar, 1994-; Linklater, Richard, 1960-; Hawke, Ethan, 1970-; Arquette, Patricia, 1968-; Linklater, Lorelei (Paramount Pictures, 2015)
A groundbreaking story of growing up as seen through the eyes of a boy named Mason, who ages from six to eighteen years old on screen.